AN ANALYSIS OF STUDENTS’ SPEAKING ANXIETY IN ACADEMIC SPEAKING CLASS - Maria Eva Damayanti; Listyani Listyani (ELTR Journal, 2020)
The study aimed to gain information about what made students felt anxious and what factors triggered students’ speaking anxiety in Academic Speaking class in English Language Education Program (ELEP) in a private university in Central Java, Indonesia. The participants of the study were 52 second-year ELEP students. A close-ended and open-ended questionnaire developed from Horwitz et al, (1986) and Angelia and Listyani (2019) were administered to the participants. The findings revealed that students’ speaking anxiety in English speaking class was derived from three main factors of anxiety, i.e. communication apprehension, test anxiety and fear of negative evaluation. Moreover, as the questionnaires answers and interview data revealed, lack of vocabulary, underestimate their ability, lack of preparation, being afraid of making mistakes, and worried of being embarassed at by his/her friends had also contributed to students’ anxiety in speaking. These findings suggest that the teachers’ role is very important in this situation. Students and teachers could build a positive classroom atmosphere in order to overcome students’ anxiety.